Farm typology analysis and technology assessment: An application in an arid region of South Asia. (November 2019) - Kumar, Shalander; Craufurd, Peter; Haileslassie, Amare; Ramilan, Thiagarajah; Rathore, Abhishek; Whitbread, Anthony
Highlights: Accounting heterogeneity and complexity of target communities is needed to increase innovation adoption under drylands. A mixed-method approach helps capture complexity and heterogeneity to co-design sustainable intensification pathways. Ex ante impact analysis of targeted technologies on household types enables their greater acceptance. Rapid digital appraisal of livelihood assets could identify households for technology targeting. Abstract: The design and diffusion of context-specific technologies is centrally important in the multi-dimensional, complex farming systems in arid and semi-arid regions. This paper uses a mixed-method framework to characterize the complexity and heterogeneity of smallholder farming systems and identifies constraints to and opportunities for sustainable intensification. Specifically, the study: (i) characterized farm household typologies based on the diversity of livelihood assets; (ii) co-designed context- specific interventions through an iterative participatory process; and (iii) ex-ante evaluated such interventions to inform multiple stakeholders. We explored farming system diversity using data from 224 farm households in western Rajasthan, India. Employing multivariate statistical techniques and participatory validation, we identified 7 distinct farm household types. Participatory appraisal with multiple stakeholders revealed heterogeneity across farm household types. For instance, the interest of farmers in integrating perennial fruit trees even among the rainfed farm household types markedly varied: household type 1 preferred the multipurpose forestry tree, khejri which requires low labor inputs; household type 2 preferred market-oriented horticulture production; household type 3 did not opt for perennials but for small ruminants; and household type 4 (dominated by women) opted for small horticulture kitchen gardens. The study demonstrated the utility of a mixed-methods approach that addresses multi-dimensional heterogeneity to generate insights and assist in co-designing locally appropriate technologies across different farm types and agro-ecological regions to achieve sustainable intensification.